Підвищенння конкурентоспроможності підприємства - Джух, Тетяна Ігорівна; Михайленко, Ольга Валеріївна; Аліпатова, Марія Русланівна (My University, 2021)
Будь-який господарюючий суб’єкт у конкурентних умовах для результативного функціонування та оцінювання своїх перспектив на майбутнє має оцінювати ступінь власної конкурентоспроможності. Маючи інформацію про особисті конкурентні позиції, промислові фірми отримують можливість розкрити свої переваги, вибрати правильну тактику поведінки та стратегію, що відповідає реаліям новітніх ринкових процесів. Основами конкурентних переваг підприємств є соціально-економічна та прогресивна технологічно-організаційна бази, вміння аналізувати та вчасно вживати заходів щодо укріплення конкурентних переваг. У статті проаналізовано шляхи підвищення конкурентоспроможності підприємств України. На сучасному етапі розвитку національної економіки основним питанням, яке має бути вирішено, є розроблення ефективних фасилітаторів та механізмів, що сприятимуть підвищенню рівня конкурентоспроможності вітчизняних виробників на ринку, а також гарантуватимуть загальне зміцнення економічного становища України. Метою статті є визначення шляхів підвищення конкурентоспроможності підприємства; порівняння інструментів, які дають змогу знайти свої слабкі сторони, усунення яких може підвищити рівень конкурентоспроможності організації. Стратегічна мета передбачає підвищення конкурентоспроможності вітчизняної економіки на основі інновацій, що створить переваги для вітчизняних виробників, щоб конкурувати з опонентами на внутрішньому та міжнародному ринках, а також допоможе Україні посісти одне з перших місць серед розвинених країн Any business entity in a competitive environment must assess the degree of its own competitiveness in order to function effectively and assess its prospects for the future. Having information about personal competitive positions, industrial firms have the opportunity to reveal their advantages, choose the right tactics of behavior and strategy, true to the realities of the latest market processes. The basis of competitive advantages of enterprises is the socio-economic and progressive technological and organizational base, the ability to analyze and take timely measures to strengthen competitive advantages. The article analyzes ways to increase the competitiveness of Ukrainian enterprises. At the current stage of development of the national economy, the main issue to be addressed is the development of effective facilitators and mechanisms that will increase the competitiveness of domestic producers in the market and will guarantee the overall strengthening of Ukraine’s economic situation. The purpose of the article is to identify ways to increase the competitiveness of the enterprise. Compare the tools that allow you to find your weaknesses, the elimination of which can increase the competitiveness of the organization. The strategic goal is to increase the competitiveness of the domestic economy through innovation, which will create advantages for domestic producers to compete with opponents in domestic and international markets, and help Ukraine to take one of the first places among developed countries. Competitiveness is a key concept that is actively used in theory and practice of management, is a multifaceted concept, which translated from Latin means rivalry, the struggle to achieve the best results. This opens for Ukraine the possibility of transition to world standards of rational and reasonable energy consumption, development of natural resources, raising the level of technology, legal protection of intellectual property. The ultimate goal of these shifts is to create progressive and competitive innovative products on world markets. It should be noted that in the context of globalization and ever-increasing competition, the basis of competitiveness is innovation, which allows countries with innovative competitive advantages to take their rightful place in the world community.
Keywords: конкурентоспроможність; підприємство; підприємство; потенціал підприємства; стабільне функціонування; competitiveness; enterprise; activity; the potential of the enterprise; stable operation; кафедра обліку і аудиту